An integrative review on the information and communication needs of parents of children with cancer regarding the use of complementary and alternative medicine - Trine Stub; Agnete E. Kristoffersen; Grete Overvåg; Miek C. Jong (BMC, 2020)
Abstract Background Parents often choose Complementary and Alternative Medicine (CAM) as a supportive agent with the aim to reduce cancer treatment-related symptoms in their children. Therefore, it is necessary to understand parents´ information and communication needs regarding CAM. The aim of the present study was to review the research literature as to identify the information and communication needs of parents of children with cancer, and the children themselves, regarding the use of CAM. Methods An integrative systematic review design was chosen. Searches were performed in AMED, CAMbase, CINAHL (Ebsco), EMBASE, PubMed and PsycInfo, Theme eJournals and Karger. The search was limited to studies published in English, German, Dutch, and the Scandinavian languages. Using predefined inclusion and exclusion criteria, two reviewers independently screened the title and abstracts of the relevant papers. A data extraction form and critical appraisal checklists were used to extract data for analysis, and a mixed methods synthesis was applied. Results Out of 24 studies included, 67% were of quantitative and 33% of qualitative study design. Five main themes emerged from the analysis of 21 studies: Information on CAM, sources of CAM information, communication about CAM, informed decision-making on CAM, and Risk/benefit of CAM. The majority of the parents did not disclose the CAM use of their children because they feared negative reactions from the attending oncologist. To make informed treatment decisions for their children, parents wanted unbiased information about CAM and would act accordingly. They demand open communication about these modalities and respect for the family's autonomy when choosing CAM for their children. Conclusion There is an urgent need for parents of children with cancer for high quality information on CAM from reliable and scientific sources. Development of authoritative evidence-based decision tools is thus warranted to enable health care professionals and parents of children with cancer to make well informed, individual decisions concerning CAM.